Suillus foetidus (Boletales, Basidiomycota), a new species from northeast China - Qi, Liangliang; Fu, Yongping; Wang, Fengjian; Song, Bing; Li, Yu (Phytotaxa, 2016)
A new species, Suillus foetidus, is described based on morphological and molecular evidence. It can be distinguished from other known species of the genus Suillus in having a dry brown pileus, a taupe without ring stipe, decurrent hymenophore which change to greenish blue when exposed and presence of clamp connections.The novelty of S. foetidus is confirmed by molecular evidence from the nucrDNA internal transcribed spacer regions (ITS). Original biotope photographs, line drawings of microscopic structures and a detailed description of sporocarp are provided.